Dynamic interactive 3D mobile navigation aid - Adamu, Abubakar Ibrahim; Mantoro, Teddy; SHAFI’I, M.A. (Little Lion Scientific Islamabad Pakistan, 2012)
This paper presents the mechanism of multi-user navigation interaction in real-time as a high-priority objective in improving mobility services efficiency and effectiveness, and investigate the support of threedimensional representation in mobile device in aiding interactive navigation in an unknown environment. The paper is based on the fact that the use of 3D representation in mobile device is more intuitive than the conventional 2D representation. Unfortunately, Mobile devices are small devices, and that is why there are mobile, as a result, 3D dataset in mobile device might overload its performance. Even though, certain techniques were seen in many research on tackling this problems, yet, when it comes to the navigation aid the predominant 3D mobile navigation system are not interactive in real-time, that is a user will not be aware of other users while on-the-go and both using mobile navigation aid in the same environment. We provide an interactive navigation techniques for finding the shortest path to a desire destination and also been able to interact with an (agent if it’s another user) or (object in terms of point or destination) in realtime with the help bi-A* pathfinding algorithm and voronoi diagram. The use of bi-A* Algorithm is to establish a forward and backward search for a destination or a position of users, while the use of voronoi diagram is to establish points and region within the navigation environment. The result of our finding indicate that information in three-dimension for navigation aid in mobile device is more intuitive and experimental result shows that multi-user interaction with support of 3D representation in mobile devices helps in aiding number of user going around within an environment an been able to be aware of their movement in real-time. This approach is unique because it provides visualization of 3D representation (map) in mobile devices’ which assists users to navigate interactively.